TINJAUAN TERHADAP PUTUSAN MAHKAMAH KONSTITUSI TENTANG STATUS ANAK LUAR NIKAH - Hidayati Fitri (JURIS (Jurnal Ilmiah Syariah), 2018)
Child protection problems nowadays are very bad and need effective strategy. From domestic problems up to those in society make children less protected, and cannot grow well. Lots of school dropouts, infant and toddler mortality, domestic and institutional violation and child exploitations are some indications poor child protection program. This study, therefore, is interested to discuss the phenomena in order to describe the roles and participation of parents, families and governments dealing with the issue of child protection. By administering questionnaire to a number of respondents living in Kecamatan Koto Tangah, this qualitative descriptive study found that the residents there did not have sufficient understanding toward the child welfare and protection as the constitution demand them to do.